Effect Of Red Dragon Fruit Skin Extract On The Growth Of Treponema denticola Biofilm - Sebastian Marco Somawihardja; Mikha Sundjojo (Scientific Dental Journal, 2025)
Background: Periodontitis can decrease a person's quality of life by causing tooth loss making it difficult to eat and decreases the level of self-confidence. Treponema denticola plays an important role in the occurrence of periodontitis. The skin of red dragon fruit (Hylocereus polyrhizus) contains secondary metabolites which are expected to reduce the formation of biofilms that cause periodontitis. Objective: To determine the effect of red dragon fruit peel extract on Treponema denticola biofilm formation. Methods: Laboratory experiment using post-test control group design in vitro with biofilm assay method. Using red dragon fruit peel extract with concentrations of 100%, 50%, 25%, 12.5%, 6.25%, 3.125%, and 1.5625%, chlorhexidine 0.2% as a positive control, and BHI-B as a negative control. The extract was distributed into well plates and incubated for 1, 3, and 24 hours. Biofilm optical density was read using a microplate reader. Results: The normality test results using the Shapiro-Wilk method at the incubation period of 1 hour, 3 hours, and 24 hours showed that the data were normally distributed (p>0.05). The results of the one-way ANOVA test for the three incubation periods showed significantly different data (p<0.05) with p=0.000. The results from Tukey HSD Post-Hoc test showed differences in significance at each concentration at each incubation period. Conclusion: Red dragon fruit peel extract can inhibit the formation of Treponema denticola biofilm.